Age of peak performance in Olympic sports: A comparative research among disciplines - Longo, A. F.; Siffredi, C. R.; Cardey, M. L.; Aquilino, G. D.; Lentini, N. A. (Journal of Human Sport & Exercise, 2016)
This research aimed to study the ages of peak performance in Olympic sport disciplines, and to distinguish age groups among them. The ages (in decimal years) of athletes with the best performances at the 2012 Summer Olympics were considered (n = 3548). A total of forty sport disciplines were included; the athletics events were classified in six disciplines: Sprint, Middle-distance, Long-distance, Combined, Jumping and Throwing. A full statistical summary was produced. A regression tree was proposed for each gender to discriminate groups of sport disciplines according to age. The ages ranged from 14.0 to 52.8 years. The 72% of the athletes aged between 20 and 30 years, and the 99% aged below 40 years. The mean ages for men and women were 27.0 and 26.2 years, respectively. The regression tree analysis generated four groups of sport disciplines in men, and five in women. In men, the mean ages of the groups were: Group 1 = 24.4, Group 2 = 25.9, Group 3 = 28.0 and Group 4 = 30.8. In women, the mean ages of the groups were: Group 1 = 19.9, Group 2 = 22.7, Group 3 = 24.6, Group 4 = 26.5 and Group 5 = 28.3. The combat, gymnastics and swimming disciplines located mostly in the youngest groups in men; a similar tendency was evidenced in women, except for the combat sports. Apart from Combined, all athletics disciplines located in the groups 4 and 5 in women. On the contrary, these disciplines sited mainly in the groups 1 and 2 in men. All game and nautical sports placed in the two eldest groups in both genders, excluding women Water Polo.